Prognostic significance of p53 protein accumulation in stage pT1 transitional cell carcinoma of the bladder - (:unkn) unknown (My University, 1999)
Objective: Mutations in the tumour suppressor gene p53 results in the production of a mutant type, dysfunctional p53 protein which can readily be detected in the cell nucleus by immunohistochemical staining. This study aims to investigate the association of nuclear p53 protein accumulation with the clinical outcome of stage pT1 transitional cell carcinoma of the bladder which is renowned for high rates of recurrence and progression. Methods: TUR samples of the tumours from fifty-two patients with primary stage T1 bladder cancer were analyzed immunohistochemically using the standard avidin-biotin peroxidase method for nuclear p53 accumulation. Status of p53 immunostaining was correlated with tumour recurrence, disease progression and three-year survival of each patient. Results: The rate of tumour recurrence in pT1 bladder cancer was 36% in patients with tumours stained negatively for p53 protein and 78% in patients with tumours stained positively for p53 protein. Disease progression was seen in 15% of p53 (-) patients and in 56% of p53 (+) patients. Conclusions: In stage pT1 bladder tumours p53 nuclear accumulation indicates higher rates of tumour recurrence and disease progression. Accordingly, in patients who have pT1 bladder tumours with nuclear p53 accumulation, institution of more aggressive therapy should be considered and early radical therapeutic modalities should be offered to these patients.